2019
DOI: 10.21273/hortsci13828-18
|View full text |Cite
|
Sign up to set email alerts
|

Hairy Vetch and Livestock Compost Improve Soil Carbon and Nitrogen, and Fresh-market Tomato Yield

Abstract: Cover crops and compost application may influence soil quality and productivity of fresh-market tomatoes. The effects of hairy vetch (HV) (Vicia villosa Roth) and livestock compost on soil C and N stocks, N availability, and tomato yield were evaluated for 2 years in a plastic high tunnel. Averaged across years, soil C and N stocks increased in plots incorporating hairy vetch and compost more than in plots with no hairy vetch and compost. When compared with baseline stocks (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…In both years, HVI was the most effective treatment in increasing STN. The positive effects of HVI on STN shown in Table 4 agreed with the results of our previous study [25] where the effects of HV (incorporation) were compared to those of livestock compost. In that study, HV incorporation showed 7.29% greater STN stock than the bare treatment (no HV and compost) and a 17.3% increase of STN stock compared with the baseline stock (initial STN stock measured before any treatment application).…”
Section: Soil Total Nsupporting
confidence: 89%
See 1 more Smart Citation
“…In both years, HVI was the most effective treatment in increasing STN. The positive effects of HVI on STN shown in Table 4 agreed with the results of our previous study [25] where the effects of HV (incorporation) were compared to those of livestock compost. In that study, HV incorporation showed 7.29% greater STN stock than the bare treatment (no HV and compost) and a 17.3% increase of STN stock compared with the baseline stock (initial STN stock measured before any treatment application).…”
Section: Soil Total Nsupporting
confidence: 89%
“…Araki et al [17] reported greater tomato yield and plant growth with HV mulch than with bare fallow. Likewise, Muchanga et al [25] reported greater marketable and total yields and shoot biomass with HV incorporation than with the bare fallow.…”
Section: Effects Of Cover Crop Residue Management On Tomato Yield N mentioning
confidence: 93%
“…Although cover crops have occasionally been shown to reduce vegetable yield (Leavitt et al, 2011), we found that the cover crop mixtures and management strategies demonstrated in this experiment did not reduce pepper yield relative to bare fallow. In one instance, red clover treatments in Rosemount Y1increased marketable yield relative to the bare control, consistent with previous studies of solanaceous crops (Abdul-Baki et al, 1996;Muchanga et al, 2019). Increased weight of marketable fruits is desirable because larger fruits are more likely to meet the highest USDA grade, 'Fancy', and can be sold for a higher price (USDA, 2005).…”
Section: Discussionsupporting
confidence: 79%
“…Tao et al [68] observed increased soil organic matter and total N with the addition of hairy vetch on a loam soil. Muchanga et al [69] reported a 3% increase in C content over a two-year period with hairy vetch as a cover crop in a high-tunnel tomato system. Harun [70] showed a 26% increase in soil organic C with winter wheat compared to control in a laboratory study on a Cumberland silt loam (fine, mixed, semiactive, thermic Rhodic Paleudalfs) in Tennessee.…”
Section: Total Carbon and Nitrogenmentioning
confidence: 99%